The Diagnostic Performance of the 2010 American College of Rheumatology/European League Against Rheumatism Classification Criteria for Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Yu-Hui ZHANG; Wei-Min SONG; Jian-Hong SUN; Jia-Chuan XIONG; Guixiu SHI4 (Archives of Rheumatology, 2013)
Objectives: This study aims to assess the diagnostic performance of the 2010 American College of Rheumatology (ACR) European League Against Rheumatism (EULAR) classification criteria for rheumatoid arthritis (RA). Patients and methods: Between January 2010 and November 2012, an electronic search was conducted using MEDLINE (via PubMed), EMBASE, and Cochrane CENTRAL to find studies related to the diagnostic performance of the 2010 ACR/EULAR classification criteria for RA in patients with inflammatory synovitis. Subgroup analyses were performed according to the adopted gold standards. The sensitivity and specificity of the 2010 criteria were extracted or calculated. Summary receiver operating characteristic (sROC) curves were drawn to evaluate the differences between the 2010 and 1987 criteria. Results: We found 10 studies which were eligible for inclusion. Based on the 2010 criteria, the pooled information showed a sensitivity of 0.804 (95% confidence interval [CI]; range 0.737 to 0.857) and a specificity of 0.556 (95% CI; range 0.417 to 0.687) in the methotrexate (MTX) group, a sensitivity of 0.706 (95% CI; range 0.585 to 0.803) and a specificity of 0.691 (95% CI; range 0.583 to 0.782) in the disease-modifying antirheumatic drug (DMARD) group, and a sensitivity of 0.901 (95% CI; range 0.856 to 0.933) and a specificity of 0.539 (95% CI; range 0.429 to 0.645) in the expert group. The sensitivity and specificity were pooled under the bivariate binomial mixed model in this review due to the heterogeneous nature of the data. Compared to the 1987 criteria, the 2010 criteria showed a higher sensitivity, lower specificity and similar accuracy rate with more accuracy rate in the MTX group, compared the DMARD and expert groups. Conclusion: The 2010 ACR/EULAR criteria for RA have a better discriminative and diagnostic ability, higher sensitivity, and lower specificity than the 1987 criteria; therefore, we believe that it cannot be substituted for the 1987 criteria.